2016
DOI: 10.1083/jcb.201605065
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of morphine-induced synaptic alterations: Role of oxidative stress, ER stress, and autophagy

Abstract: Cai et al. demonstrate that morphine exposure dysregulates synaptic balance in the hippocampus. This effect involves a novel pathway involving ROS, ER stress, and autophagy and can be rescued by PDGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 55 publications
6
73
0
Order By: Relevance
“…Intriguingly, pretreatment of A172 astrocytes with the ER stress inhibitor, 4-PBA or transfection of human astrocytes with PERK siRNA resulted in inhibition of morphine-induced ER stress, autophagy, astrocyte activation as well as expression of proinflammatory cytokines, thereby confirming that ER stress markers lie upstream of autophagy. The present findings are in agreement with our previous report demonstrating that morphine-induced ER stress/autophagy axis was critical for synaptic impairment in hippocampal neurons [43]. Taken together, our in vitro data showed that morphine induces ER stress-mediated defective autophagy which, in turn, leads to astrocyte activation and secretion of proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Intriguingly, pretreatment of A172 astrocytes with the ER stress inhibitor, 4-PBA or transfection of human astrocytes with PERK siRNA resulted in inhibition of morphine-induced ER stress, autophagy, astrocyte activation as well as expression of proinflammatory cytokines, thereby confirming that ER stress markers lie upstream of autophagy. The present findings are in agreement with our previous report demonstrating that morphine-induced ER stress/autophagy axis was critical for synaptic impairment in hippocampal neurons [43]. Taken together, our in vitro data showed that morphine induces ER stress-mediated defective autophagy which, in turn, leads to astrocyte activation and secretion of proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies have also shown that morphine exposure resulted in synaptic injury in the hippocampal neurons and that this was mediated via the ER stress-autophagy axis [43]. The present study demonstrates that in astrocytes morphine exposure results in initiation of autophagy as well as autophagosome formation.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations